The application of theory of tethered balloons to measurement of low level winds - SAHA, K. R. (MAUSAM, 1956)
A theory of tethered balloons advanced by the author earlier (Saha '1956) for the determination of aerodynamic resistance 18 developed and applied to the measurement of low level winds up to an average height of about 350 ft above the ground. The effect of the supporting thread is discussed ill detail and the difficulty of taking the effect of the aerodynamic resistance of the thread in a variable wind distribution into a consistent theory is pointed out. An approximate solution is offered by assuming that the total resistance of the thread is the sum of the resistances of every 100 ft of the length released in a prevailing wind distribution. Certain assumptions are also made in regard to sag angle, the shape of the thread, the air density, the free lift and the diameter of the balloon ete. Winds computed from data of tethered balloon flights in accordance with the present method are compared with the results of pilot balloon flights taken almost simultaneously. Agreement is found to be fairly close and satisfactory. Divergence in a few cases may b~ due to the fact that in a turbulent atmosphere a tiny pilot balloon like the one used in the present experiments for its low rate of ascent cannot maintain its uniform rate of ascent as assumed and is liable to yield winds that are not quite dependable.